Formal Methods for Multicore Programming: 15th International School on Formal Methods for the Design of Computer, Communication, and Software Systems, SFM 2015, Bertinoro, Italy, June 15-19, 2015, Advanced Lectures - Bernardo, Marco (Springer, 2015)
This book presents 5 tutorial lectures given by leading researchers at the 15th edition of the International School on Formal Methods for the Design of Computer, Communication and Software Systems, SFM 2015, held in Bertinoro, Italy, in June 2015. SFM 2015 was devoted to multicore programming and covered topics such as concurrency and coordination mechanisms, architecture and memory models and type systems.